Fungicides alter the distribution and diversity of bacterial and fungal communities in ginseng fields. Issue 1 (1st January 2021) - Ma, Guilong; Gao, Xinxin; Nan, Jie; Zhang, Tingting; Xie, Xiaobao; Cai, Qi
ABSTRACT: The present study was focused on comparison of four typical fungicides in ginseng field to evaluate the impact of the different fungicides on the soil bacterial and fungal communities' composition and diversity by using high-throughput sequencing. Five treatments were designed comprising carbendazim (D), dimethyl disulfide (E), dazomet (M), calcium cyanamide (S), and control (C). The application of fungicide obviously altered the distribution of dominant fungal and bacterial communities and remarkably decreased the diversity (1099-763 and 6457-2245). The most abundant Proteobacteria obviously degenerate in fungicide-treated soil and minimum in E (0.09%) compared to control (25.72%). The relative abundance of Acidobacteria was reduced from 27.76 (C) to 7.14% after applying fungicide and minimum in E. The phylum Actinobacteria are both decomposers of organic matter and enemies of soil-borne pathogens, elevated from 11.62 to 51.54% and are high in E. The fungi community mainly distributed into Ascomycota that enriched from 66.09 to 88.21% and highin M and E (88.21 and 85.10%), and Basidiomycota reduced from 21.13 to 3.23% and low in M and E (5.27 and 3.23%). Overall, environmentally related fungicides decreased the diversity and altered the composition of bacterial and fungal communities, highest sensitivity present in dimethyl disulfide-treated soil. Graphical abstract: uf0001